(untitled) (Global Journal of Management and Business Research, 2023)
Since they typically live hand-to-mouth, poor households are disproportionately affected by inflation. Even modest price increases have a significant impact on poorer families’ consumption compared to wealthier families. In addition, unchecked inflation creates poverty traps. It forces low-income families to eat lower-quality food to prevent famine, which can have an impact on the cognitive development of their kids. Nowadays, that is a serious issue in our country, so the researcher has chosen that topic. The study is based on primary as well as secondary data, which was collected by a convenient sampling method from 203 respondents through a structured questionnaire in Saurashtra; The researcher used different tests and tools, including pilot surveys, a reliability test (the results of which are given below), and the above tools based on different objectives. The researcher used the Mann Whitney U test (U) for Gender and Place and the Kruskal Wallis test (H) in other cases. It is also seen that 63% of respondents say that inflation is increasing due Inflation has increased due to the current Russia-Ukraine war, and at present, there is a problem of inflation in most of the countries of the world because 85% of respondents agree with this sentence.